2008
DOI: 10.1387/ijdb.082655am
|View full text |Cite
|
Sign up to set email alerts
|

The enigmatic role of the ankyrin repeat domain 1 gene in heart development and disease

Abstract: It has been proposed that the ankyrin repeat domain 1 (ANKRD1) factor (also known as CARP) plays a critical role in transcriptional regulation, myofibrillar assembly and stretch sensing during heart development and cardiac insults. ANKRD1/CARP has also been reported to negatively regulate cardiac gene expression in cell-based promoter-reporter assays. Consequently, rapid up-regulation of the ankrd1 gene in myocardium in response to developmental stimuli or pathological insults has tended to be interpreted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 88 publications
(135 reference statements)
4
81
1
Order By: Relevance
“…Overexpression and increased protein levels of ANKRD1 in failing myocardium have been previously described, suggesting that this factor may significantly RNA-Seq and the cardiomyocyte cytoskeleton in HF I Herrer et al contribute to pathological heart remodeling. 28,29 It is surprising, however, that most investigations have focused on the induction of ANKRD1 expression in animal models and in vitro cultured primary cardiomyocytes. Thus, our study confirmed previous studies and provided accurate data about the increased ANKRD1 levels in human HF samples.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression and increased protein levels of ANKRD1 in failing myocardium have been previously described, suggesting that this factor may significantly RNA-Seq and the cardiomyocyte cytoskeleton in HF I Herrer et al contribute to pathological heart remodeling. 28,29 It is surprising, however, that most investigations have focused on the induction of ANKRD1 expression in animal models and in vitro cultured primary cardiomyocytes. Thus, our study confirmed previous studies and provided accurate data about the increased ANKRD1 levels in human HF samples.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these molecular characteristics, it is generally thought that many proteins with ankyrin repeats may play roles in integrating signals from multiple protein-protein interactions. Various kinds of ankyrin repeat-containing proteins have been identified as nuclear receptor cofactors that interact with nuclear receptors to enhance or suppress transcription of target genes (34). These reports enabled us to speculate that the Anox product may facilitate initiation of dInR transcription through interaction with dFOXO.…”
Section: Discussionmentioning
confidence: 99%
“…When some prominent species of the proteins up-regulated more than 1.5-fold in the TAC model are analyzed in detail, the most pronounced hits, ANKRD1 is preferentially expressed in hearts and was previously shown to be up-regulated in response to stress and hypertrophic stimuli and in heart failure. 40 Periostin was also reported to be linked to cardiac hypertrophy due to myocardial infarction and was shown to induce proliferation of differentiated cardiomyocytes. 41 FHL1 was suggested to play an important role in biomechanical stress responses involved in cardiac hypertrophy and disease.…”
Section: Quantitative Characterization Of An In Vivo Mousementioning
confidence: 99%